PENGEMBANGAN MODUL PEMBELAJARAN MATA PELAJARAN PEMELIHARAAN MESIN KENDARAAN RINGAN KELAS XI TKR SMK NEGERI 2 PADANG SIDEMPUAN - Erzeddin Alwi; Munawir Harahap; Donny Fernandez; Milana Milana (Ensiklopedia Education Review, 2022)
The lack of learning resources and continued reliance on a teacher-centered learning approach for issues related to light vehicle engine repair served as the driving force for this study. The goal of this study is to provide a trustworthy and useful module for the Light Vehicle Engine Maintenance course for students in the Vocational School SMKN 2 Padangsidempuan's 11th grade Light Vehicle Enginering (Teknik Kendaraan Ringan/TKR) Study Program. The research and development technique is this kind of study. The approach is a four-step process called the Define, Design, Development, and Disseminate. The study's participants were 11th-grade students at the vocational school SMKN 2 Padangsidempuan's Light Vehicle Engineering (Teknik Kendaraaan Rimgan/TKR) Study Program. To evaluate the accuracy and usefulness of the data gathered, a questionnaire assessment sheet was employed during the data gathering procedure.Keywords: Module, Light Vehicle Engine Maintenance